Endolymphatic hydrops asymmetry distinguishes patients with Meniere’s disease from normal controls with high sensitivity and specificity - Noh, Tae-Soo; Park, Moo Kyun; Lee, Jun Ho; Oh, Seung Ha; Kim, Ji-hoon; Song, In Chan; Suh, Myung-Whan (Frontiers in Neurology, 2023)
Background: Many endolymphatic hydrops (EH) MRI studies in the literature do not include a normal control group. Consequently, it remains unclear which outcome measure in EH MRI can most effectively distinguish between MD patients and normal controls. Methods: Gadolinium-enhanced EH imaging was performed to quantitatively evaluate the extents of hydrops in MD patients and age-/sex-matched normal controls. Four hours after intravenous injection of contrast agent , MRI was performed using a 3-T MR platform fitted with a 32-channel phased-array coil receptor. MR images (10-15 slices) covering an inner ear were 3D-stacked. Analyses of all images that included the vestibule or the cochlea yielded the volumes (in µL) of the endolymphatic and perilymphatic spaces. Results: For the vestibule, they were significantly greater EH% in ipsilateral (52.4 ± 12.5) than in contralateral MD ears (40.4 ± 8.5, P = 0.001) and in ipsilateral MD ears than in control ears (42.4 ± 13.7, P = 0.025). For the cochlea, the values were slightly higher EH% in ipsilateral MD ears (49.7 ± 10.4, P = 0.061) but did not significantly differ from contralateral (41.3 ± 12.6) or control ears (39.6 ± 18.9, P = 0.858). In the MD group, the EH asymmetries were 12.0 ± 10.2% (vestibule) and 8.4 ± 8.6% (cochlea), significantly larger than those of controls. Compared to conventional semiquantitative grading or quantitative EH% analysis, EH asymmetry may better distinguish MD patients from normal controls.Quantitative hydrops volumetric analysis yields clinically relevant information on inner ear function.